Advances in yam and cassava nematology research at IITA - Coyne, D.; Mudiope, J.; Hugues, B. (2003)
Progress in pest management on cassava (Manihot esculenta) in Africa has witnessed remarkable achievements over recent years in the management of African cassava mosaic virus, cassava mealy bug, cassava green mite and overall germplasm improvement for yield improvements. From the scant information available, root-knot nematodes appear to pose potentially serious constraints to cassava production across Africa. Under heavy infection, 98 % yield losses have been reported and in a survey in Uganda, 100 % of fields observed were infected, yet little attention has been paid to this potential constraint. On yam (Dioscorea spp.), the yam nematode, Scutellonema bradys, is a primary constraint to production and increased adoption of the crop in West Africa. In East Africa the importance of yam has declined over the last few decades and efforts to increase its promotion are hampered by nematode pests. S. bradys has to date not been observed in East Africa, but Pratylenchus sudanensis has been identified, causing similar damage to S. bradys. Meloidogyne spp. also appear to be particularly damaging to introduced, high-yielding yam lines. Screening against these nematodes is currently in progress. Research at the IITA in East and West Africa has made progress towards improved knowledge on these pests. These include initiating work on the biology and epidemiology of P. sudanensis on yam, improving our knowledge of Meloidogyne spp. important on cassava, expanding information on the distribution and incidence of nematode pests on these crops and development of management options against them.